Kajian Terhadap Pemberian Hak Garap Atas Tanah Di Kawasan Hutan Lindung: (STUDI DESA PENGOROS) - Muhammad Andry Kurniawan; Arief Rahman (Fakultas Hukum Universitas Mataram, 2022)
This study describes the process of granting rights to cultivate over protected forest area to neighbour community in Pengoros Village. This study is a normative-empirical one, with statute, conceptual, and sociological approach. Protected forest area is an area that is free from any activity as its existence is protected by the state, in 2002, the Government established the forest area as a protected one according to the Decree of Minister of Forestry No 8214/kpts-II on September, 9th 2002 of the Establishment of Forest Area. This establishment indicated that any activity is restricted over the land. Normatively, the rights granted by the Sub-District Government had been valid as the grants had been granted before the establishment of protected forest area. On the contrary, the establishment of the protected forest area is argued as legally invalid as according to the Law No 41 of 1999 of Forestry, protected forest area is established over land that is non-forest and ownerless.